Dissolution test of various low-dose acetylsalicylic acid preparations marketed in Indonesia (Medical Journal of Indonesia, 2009)
Aim To compare the dissolution profi les of various enteric-coated low-dose acetylsalicylic acid (ASA) tablets marketed in Indonesia. Methods The dissolution study was carried out according to US Pharmacocopoeiae (USP) /European Pharmacopoeiae, method A, using USP apparatus 1 (basket) 100 rpm, with 2 media: 0.1 N HCl, 120 minutes for acid stage, and phosphate buffer pH 6.8, 90 minutes for buffer stage. The sampling points were 120 minutes for the acid stage, and every 10 minutes until 90 minutes for the buffer stage. The acetylsalicylic acid was assayed using spectrophotometry at 280 nm for the acid stage, and at 265 nm for the buffer stage. The free salicylic acid was determined only at the end of the buffer stage with HPLC method. There were 6 test products (Cardio Aspirin® 100 mg, Aptor® 100 mg, Ascardia® 80 mg, Thrombo Aspilet® 80 mg, Astika® 100 mg and Farmasal® 100 mg), 3 batches for each product, and 6 units for each batch. Results The amount of ASA released from each ASA product tested at the end of acid stage (120 minutes) ranged from 1.79% for Cardio Aspirin® to 6.92% for Thrombo Aspilet®, all conformed to the compendial requirement for enteric-coated product (< 10%). The amount of salicylic acid observed at the end of the dissolution test ranged from 3.47% for Cardio Aspirin® to 10.90% for Astika® and 11.90 % for Thrombo Aspilet®. Thrombo Aspilet® showed sustained-release properties, causing high variability in ASA release, such that one of the 3 batches tested did not fulfill the compendial requirement of more than 75% (the release was only 55.11%). High variability in ASA release between batches was also found with Farmasal® at 10, 20, and 30 minutes in buffer medium. The lowest effective dose of ASA as an antiplatelet drug for longterm use is 75 mg of plain ASA, and this is equivalent to 100 mg of enteric-coated ASA. Conclusions All of the low-dose ASA preparations marketed in Indonesia are enteric-coated products, while Thrombo Aspilet® is not only an enteric-coated but also a sustained-release product. Cardio Aspirin®, followed by Aptor®, has the right dose for low-dose enteric-coated preparation (100 mg), produces consistent ASA release between batches, and the most stable towards deacetylation (antiplatelet inactivation). (Med J Indones 2009;18:159-64)